Optical approach for the efficient data volume handling in experimentally encrypted data - Trejos, Sorayda (2016)
Experimental optical procedures generate a tremendous amount of data, which must be then processed for any practical application. We present a new optical approach in terms of the data volume for the efficient handling of multiple data obtained from an experimental cryptosystem. In order to achieve this goal, we use the combination of optical filtering and optical scaling of the experimentally registered data. The intention is to reduce by optical means the amount of data to be managed. We define a so called 'efficiency factor' to describe the effectiveness of the approach. We find that volume reduction depends on this factor and the number of objects to be processed. We achieved substantial data volume reductions up to 94.24%. We introduce the basic concepts as well as experimental results that support both the feasibility and the applicability of our approach.